A astronomia no ensino da matemática: aplicações na educação básica. - Ribeiro, Rodrigo Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
It is no secret that issues related to technologies such as Robotics, Programming or Astronomy, arouse interest in young people and children, and can be considered as inducers for pedagogical work in various sciences, including Mathematics. Although Astronomy is considered one of the first study sciences of man, it does not find its proper place within a conventional school curriculum. Students complete the basic teaching cycle, without even having access to essential concepts of science, making room for traps caused by waves of disinformation, such as conspiracy theories, fake news, negationism, post-truth or belief in alternative facts. In this sense, for the development of the theme, it was decided to carry out a descriptive research, presenting the point of view of specialists in the area and the results of observation carried out during the graduation's internship, regarding the teaching practices of the “School Project” from Alpha Lumen Institute, an NGO that works with high-skill students in São José dos Campos. Thus, due to the situations raised, this work comes to demonstrate the existence of an interdisciplinarity between Astronomy and Mathematics, as well as the results of a teaching practice that builds this interconnection.

Não é segredo que assuntos relacionados a tecnologias como Robótica, Programação ou Astronomia, despertam interesse em jovens e crianças, podendo ser considerados como indutores para um trabalho pedagógico em diversas ciências, entre elas a Matemática. Muito embora a Astronomia seja considerada uma das primeiras ciências de estudo do homem, ela não encontra seu devido espaço dentro de um currículo escolar convencional. Estudantes tem concluído o ciclo básico de ensino, sem sequer ter tido acesso a conceitos essenciais da ciência, abrindo espaço para ciladas provocadas por ondas de desinformação, como teorias da conspiração, fake news, negacionismo, pós-verdade ou crença em fatos alternativos. E nesse sentido, para o desenvolvimento do tema, optou-se pela realização de uma pesquisa descritiva, apresentando o ponto de vista de especialistas na área e os resultados de observação realizada durante estágio de licenciatura, referente as práticas de ensino do “Projeto Escola” do Instituto Alpha Lumen, uma ONG que trabalha com estudantes de altas habilidades em São José dos Campos. Dessa forma, em virtude das situações levantadas, esse trabalho vem demonstrar a existência de uma interdisciplinaridade entre a Astronomia e a Matemática, bem como os resultados de uma prática de ensino que construa essa interligação.
Astronomy in the teaching of mathematics: applications in basic education.
La astronomía en la enseñanza de las matemáticas: aplicaciones en la educación básica.
Keywords: Math teaching; Astronomy; High skills; Matemática Estudo e ensino; Astronomia Estudo e ensino; Abordagem interdisciplinar do conhecimento na educação